The development of inclusive education management model: Practical guidelines for learning in inclusive school - Iva Evry Robiyansah; Mudjito Mudjito; Murtadlo Murtadlo (Intelektual Pustaka Media Utama, 2020)
This research aimed to explore the current conditions, problems, and needs in the implementation of inclusive education, to examine the best model of the implementation of inclusive education and to investigate the effectiveness of the inclusive education model. This research was mixed method researchs which was conducted in three stages. Stage one was exploring the current conditions, problems, and the needs on inclusive education implementation. Stage two was formulating an inclusive education learning model and stage three was determining the efficiency of the inclusive education model. Findings reveal that students and learning are the biggest obstacle in implementing inclusive education, while management, students, and learning are the most important factors to be considered in implementing inclusive education model. Based on the findings, the whole school inclusive education model was developed which consisted of three stages namely input, process, and output. It was suggested that during the implementation of this model collaboration should be emphasized.